Relationship Between Nurses Caring and Patient Satisfaction Level in The Inpatient Ward of Tobelo Regional General Hospital - Olivia Asih Blandina; Meilin Salindapen (Jurnal Manajemen Informasi dan Administrasi Kesehatan, 2025)
This study aims to analyze the relationship between nurse caring and patient satisfaction at the Tobelo Regional General Hospital. The research employs a quantitative design with a cross-sectional approach. The population of the study consists of all inpatients at the hospital in 2024, with a sample of 375 respondents selected using the Slovin formula. Data were collected through a questionnaire containing questions about nurse caring behavior and patient satisfaction levels. The results of this study are expected to provide a better understanding of the importance of nurse caring in enhancing patient satisfaction in inpatient settings. The implications of this research are anticipated to serve as a basis for improving the quality of healthcare services in hospitals, particularly in enhancing nurse-patient interactions and attention. This study contributes to strengthening the relationship between nurse caring and patient satisfaction, as well as providing a foundation for further development in improving the quality of healthcare services in hospitals.   Keyword: patient satisfaction, nurse caring